The combined use of interleukin-6 with serum albumin for mortality prediction in critically ill elderly patients: the interleukin-6-to-albumin ratio - Lim, Kai Yang; Wan Muhd Shukeri, Wan Fadzlina; Wan Hassan, Wan Mohd Nazaruddin; Mat Nor, Mohd Basri; Hanafi, Muhammad Hafiz (Jaypee Brothers Medical Publishers (P) Ltd, 2022)
Background: The association between interleukin-6 (IL-6) and serum albumin (ALB) with mortality in critically ill elderly patients, either as stand-alone biomarkers or in combination, has been scarcely reported. We, therefore, aimed to investigate the prognostic value of the IL-6-to-albumin ratio in this special population. Patients and methods: This was a cross-sectional study conducted in the mixed intensive care unit (ICU) of two university-affiliated hospitals in Malaysia. Consecutive elderly patients (aged above or equal to 60 years) admitted to the ICU, who underwent simultaneous measurement of plasma IL-6 and serum ALB, were recruited. The prognostic value of the IL-6-to-albumin ratio was assessed by analysis of the receiver-operating characteristic (ROC) curve. Results: A total of 112 critically ill elderly patients were recruited. The outcome of all-cause ICU mortality was 22.3%. The calculated IL-6-to-albumin ratio was significantly higher in the non-survivors compared to the survivors {14.1 [interquartile range (IQR), 6.5–26.7] vs 2.5 [(IQR, 0.6–9.2) pg/mL, p <0.001]}. The area under the curve (AUC) of IL-6-to-albumin ratio for discrimination of ICU mortality was 0.766 [95% confidence interval (CI), 0.667–0.865, p <0.001] which was slightly higher than that of IL-6 and albumin alone. The ideal cut-off value of the IL-6-to-albumin ratio was above 5.7 with a sensitivity of 80.0% and specificity of 64.4%. After adjusting for severity of illness, the IL-6-to-albumin ratio remained as an independent predictor of ICU mortality with an adjusted odd ratio of 0.975 (95% CI, 0.952–0.999, p = 0.039). Conclusion: The IL-6-to-albumin ratio offers a slight improvement in mortality prediction than either of its constituent individual biomarkers and as such, it may be a potential tool to aid in the prognostication of critically ill elderly patients although this requires further validation in a larger prospective study.